2016
DOI: 10.1016/j.jep.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants used in the traditional management of diabetes and its sequelae in Central America: A review

Abstract: This review provides an overview of the medicinal plants used to manage diabetes and its sequelae in Central America and of the current scientific knowledge that might explain their traditional use. In Central America a large number of medicinal plants are used to treat this condition and its sequelae, although relatively few species are widely used across the region. For the species used to manage diabetes, there is variation in the availability and quality of pharmacological, chemical and clinical studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 162 publications
(237 reference statements)
2
64
0
5
Order By: Relevance
“…The significance of another important species, A. vera, could be explained by its trend of popular usage to cure the most common conditions. In Central America, A. vera is used for a wide range of conditions, such as diabetes, skin problems, and kidney diseases [42]. The juice has long been used as a sugar substitute for patients who have problems associated with triglycerides in the blood [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of another important species, A. vera, could be explained by its trend of popular usage to cure the most common conditions. In Central America, A. vera is used for a wide range of conditions, such as diabetes, skin problems, and kidney diseases [42]. The juice has long been used as a sugar substitute for patients who have problems associated with triglycerides in the blood [42].…”
Section: Discussionmentioning
confidence: 99%
“…In Central America, A. vera is used for a wide range of conditions, such as diabetes, skin problems, and kidney diseases [42]. The juice has long been used as a sugar substitute for patients who have problems associated with triglycerides in the blood [42]. These examples indicate that the culturally important medicinal plants of Zacatecan communities are known to be effective pharmacologically, suggesting that the traditional knowledge is well founded, and that other medicinal plants used in the area are likely to be efficacious as well.…”
Section: Discussionmentioning
confidence: 99%
“…There are attempts to validate the traditional use of medicinal plants using contemporary scientific methods [109][110][111]. Multiple plant species used in traditional medicine in different parts of the world have been shown to have at least some antidiabetic activity [112]. A considerable number of plants was subjected to clinical trials and found effective.…”
Section: The Need For New Therapeutic Agentsmentioning
confidence: 99%
“…Many authors have reported traditional uses, folk medicine, phytochemistry and several studies demonstrating biological activities of P. guajava extracts [1][2][3][4][5][6]. Furthermore some papers suggest the anticancer potential of P. guajava leaf extracts by acting as inhibitors of tumor cells proliferation and motility and also acting as proapoptotic agents [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%